Influence of static mixer on the development of aerobic granules for the treatment of low-medium strength domestic wastewater - We, Angel Chyi En; Azmi, Aris; Nor Azimah, Mohd Zain; Khalida, Muda; Suryati, Sulaiman (Elsevier, 2021)
The present work investigates the feasibility of aerobic granulation for the treatment of low-medium strength domestic wastewater for long-term operation and effects of a static mixer on the properties and removal performances of the aerobic granules formed. The static mixer was installed in a sequential batch reactor to provide higher hydrodynamic shear force in enhancing the formation of the aerobic granules. Aerobic granules were successfully formed in the domestic wastewater, and the granulation treatment system was sustained for a period of 356 days without granules disintegration. Subsequent to the installation, aerobic granules with a low SVI30 of 41.37 mL/gTSS, average diameter 1.11 mm, granular strength with integrity coefficient 10.4% and regular shape with minimum filamentous outgrowth were formed. Mineral concentrations such as Fe, Mg, Ca and Na as well as composition of protein and polysaccharide in tightly bound-extracellular polymeric substance of the aerobic granules were found to be higher under the effect of the static mixer. However, no significant improvement was observed on the TCOD, NH4 þ-N and TSS removal performance. Good TCOD and TSS removal performance of above 85% and 90%, respectively and moderate NH4 þ-N removal performance of about 60% were observed throughout the study. Higher simultaneous nitrification and denitrification (SND) efficiency of 56% was observed after the installation of the static mixer, as compared to 21% prior. Therefore, it may be concluded that the installation of the static mixer significantly improved the properties of aerobic granules formation and SND efficiency but not the TCOD, NH4 þ-N and TSS removal performance.